Relationship Marketing : a Consumer Experience Approach - Baron, Steve; Conway, Tony; Warnaby,Gary (London, 2010)
The relationship between a market and a consumer is complex. Far from simply an exchange of services there is an often complex transaction of feeling, meaning, and experience. How does the study of relationship marketing interpret this? In this exciting new book the authors explore the factors of relationship marketing in its contemporary context, with the consumer in mind. From the experience of a football club supporter to experiences of gap year travel, to text messaging behavior, and to using the library, the focus of this text is on the consumer perspective.
Keywords: Relationship Marketing